Membentuk Karakter Generasi Bangsa Melalui Penggunaan Media Sosial? - Altami, Bulan; Akbar, Asep Mulyana; Maysuri, Astri; Setiawati, Setiawati (Penerbit Goodwood, 2024)
Purpose: This article discusses the impact of social media usage on character formation in a nation's generation, especially among teenagers. Methodology: This study uses a qualitative approach with interviews and observation techniques on millennials who are active users of social media. Results: This research shows that although social media can accelerate information exchange and enhance creativity, it also risks having negative impacts on the morals and ethics of adolescents. Therefore, the roles of parents, teachers, and education stakeholders are very important in guiding the younger generation to use social media wisely and responsibly. Conclusions: Social media has an enormous influence on teenagers. Without proper guidance, they are vulnerable to negative behaviors. Character education in the digital era involves parents, teachers, and the community to ensure wise use of social media, raising awareness of its positive and negative impacts. Therefore, clear guidance is required. Limitations: This study was limited to young people who are active on social media; therefore, the results may not be representative of the entire adolescent population. Additionally, the qualitative approach limits the generalizability of the findings. Contribution: This study provides insights into the impact of social media on the formation of adolescent characters. The results can be used as a basis for designing effective character education programs involving parents and educators in the wise and responsible use of social media.